Weight-management in children living with asthma: a qualitative study of the experiences of paediatric healthcare professionals. (2nd December 2019) - Clarke, Rebecca; Heath, Gemma; Pattison, Helen; Farrow, Claire
Abstract: Objective: Weight loss has been found to improve the symptoms of asthma in children who are overweight. However, many paediatric weight management programmes do not address the challenges associated with living with asthma. The aim of this study was to explore the views and experiences of paediatric healthcare professionals concerning weight management advice and support offered to families of children living with asthma. Methods : In-depth individual interviews with 10 healthcare professionals who work with a paediatric asthma population ( n  = 4 Respiratory Consultants, 3 Respiratory Nurses, 3 General Paediatricians). Data were analysed using a Framework approach. Results: Healthcare professionals highlighted that families' perceptions of weight, their approach to physical activity and nutrition, the family's social context and perceptions of asthma and asthma treatment all influence weight management in children living with asthma. Initiating weight management conversations and referring to weight management support were perceived as challenging. It was thought that tailoring weight management to the needs of children living with asthma and locating support within the community were important to the success of a family-centred intervention. Conclusions: The results highlight the added complexity of responding to excessive weight in a paediatric population with asthma. Training and referral guidance for healthcare professionals may help overcome weight management support challenges. Addressing family beliefs about the factors influencing paediatric asthma and exploring families' motivations for behaviour change may enhance engagement with weight management.